FRI0069 Neutralization of IL6 by Sirukumab (SIR) Inhibits Inflammation and Cellular Stress in a Human Vascular Surrogate System of Atherosclerosis. (9th June 2015) - Feaver, R.; Collado, S.; Hoang, S.; Berzin, E.; Armstrong, A.; Gardner, D.; Liu, H.; Mackey, A.; Manka, D.; Shealy, D.; Blackman, B.
Abstract : Background: Rheumatoid arthritis (RA) and atherosclerosis are chronic inflammatory diseases that share pathologic and molecular features. RA doubles the risk of cardiovascular disease (CVD) compared to the non-RA population. Common RA treatments are anti-inflammatory by design, but effects on CVD are unclear. Previously we reported the effect of SIR on IL6 and tumor necrosis factor (TNF) α signaling using a human endothelial cell (EC) and smooth muscle cell (SMC) co-culture system. Here we report additional analyses further characterizing effects of SIR on atherosclerotic (ATH) and oxidative (OX) stress pathways. Objectives: To examine if RA drugs decrease ATH signaling and cellular stress in vascular cells under CVD conditions. Methods: An in vitro surrogate system that co-cultures human ECs and SMCs was used to assess effects of RA drugs on vascular cells. Fluid flow conditions that drive cardiovascular health and CVD were applied. Atheroprone flow conditions were based on human hemodynamics from the carotid bifurcation, a site prone to developing atherosclerosis. The culture medium contained atherogenic risk factors including in vivo concentrations of oxidized LDL (oxLDL), soluble IL6 receptor (sIL6R), and TNF. Using RNA sequencing and microarray, we performed transcriptomic and biologic pathway analyses of surrogate system response. We compared treatments targeting pathogenic RA pathways, including anti-IL6 (SIR), anti-IL6 receptor (tocilizumab; TCZ), anti-TNF (adalimumab; ADA), and a small molecule JAK inhibitor (tofacitinib; TOF). The magnitude of pathway response was calculated as the L 2 norm of the log2 fold change of genes in the pathway. Results: The combination of atheroprone flow, sIL6R, TNF, and oxLDL (RA-CVD conditions) induced a robust response of inflammatory and OX stress pathways compared to healthy conditions (atheroprone flow without TNF and with non-oxLDL and sIL6R). The anti-IL6/IL6R treatments (SIR, TCZ) improved RA-CVD conditions by inhibiting key pathogenic pathways, including ATH signaling and NRF2-mediated OX stress. SIR attenuated the magnitude of RA-CVD response in ATH and OX stress pathways vs IgG or vehicle control the most: by 17% (adj P =0.035; Wilcoxon signed-rank test) and 34% (adj P =0.094) in ECs; and 49% (adj P =1.4e-5) and 47% (adj P =1.1e-3) in SMCs, respectively. TCZ was similar to SIR in restoring ECs and SMCs to healthy conditions in both pathways; ADA showed a weaker, similar trend compared to IL6 inhibition. TOF was not effective in suppressing (and tended to exacerbate) ATH and OX stress pathways in ECs. Conclusions: IL6 pathway inhibitors SIR and TCZ potently suppressed ATH and cellular stress in vitro. The degree of suppression suggests that these drugs may mitigate the effects of atherogenic factors sIL6R, TNF, and oxLDL. In contrast, TNF inhibitor ADA was a less effective inhibitor of key CVD pathways, while JAK inhibitor TOF tended to exacerbate CVD pathways. Collectively, the data suggest that IL6 inhibition may provide more CVD benefit compared to RA drugs targeting other pathways. Acknowledgements: Study sponsored by Janssen Research & Development, LLC, in collaboration with GlaxoSmithKline. Disclosure of Interest: R. Feaver Shareholder of: HemoShear, LLC, Employee of: HemoShear, LLC, S. Collado Employee of: HemoShear, LLC, S. Hoang Employee of: HemoShear, LLC, E. Berzin Employee of: HemoShear, LLC, A. Armstrong Shareholder of: HemoShear, LLC, Employee of: HemoShear, LLC, D. Gardner Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Development, LLC, H. Liu Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Development, LLC, A. Mackey Shareholder of: HemoShear, LLC, Employee of: HemoShear, LLC, D. Manka Shareholder of: HemoShear, LLC, Employee of: HemoShear, LLC, D. Shealy Shareholder of: Johnson & Johnson, Employee of: Janssen Research & Development, LLC, B. Blackman Shareholder of: HemoShear, LLC, Employee of: HemoShear, LLC